Developing The Gorga Batak Toba Mobile Book: A Digital Innovation for Fine Arts Practice and Education in Indonesian Higher Education - Azis, Adek Cerah Kurnia; Astuti, Tri Marhaeni Pudji; Syakir, Syakir; Haryanto, Eko (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop mobile-book teaching materials for the Nusantara Ornaments course, focusing on Toba Batak Gorga as an effort to transform the digital learning ecosystem in higher education. The research employs a research and development (R&D) method using the 4-D model—Define, Design, Develop, and Disseminate. Data were collected through observations, interviews, document analysis, and questionnaires, and were analyzed using a developmental research approach. Product trials were conducted with Fine Arts students at Universitas Negeri Medan (small group, n = 120) and students at Universitas Negeri Padang, Universitas Negeri Semarang, and Universitas Muhammadiyah Makassar (large group, n = 240). Expert validation covered four domains: cultural heritage content, learning media, visual communication design, and language (Indonesian and Toba Batak). In the Define stage, the needs analysis emphasized integrating the philosophy of Gorga with contemporary digital design techniques. The Design stage produced responsive prototypes featuring high-resolution visuals and structured learning flows, while the Develop stage incorporated interactive features to support hybrid learning. Validation results showed an overall average score of 75.85% (“Good” category), consisting of 75.86% from cultural heritage expert I, 73.79% from cultural heritage expert II, 79.14% from the design expert, and 74.61% from the linguist. These findings confirm that the developed mobile book aligns with the 4-D development procedures and meets the criteria of an innovative learning medium that provides flexible access, supports both in-class and out-of-class learning, and promotes cultural preservation by transforming the knowledge of Toba Batak Gorga into accessible digital resources. The dissemination plan includes implementation guidelines for lecturers and a mechanism for continuous improvement informed by cross-cultural learning analytics across universities in Indonesia.